Analisis Kinerja Keuangan Usahatani Cabai Merah berdasarkan Strata Lahan di Kepahiang - Refi Septarena; Bambang Sumantri; Lathifah Khairani (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
This research aims to analyze the financial performance of curly red chili farming based on different strata of land area in Suka Sari Village, Kepahiang Regency. There are not many studies that discuss the financial performance of farming, especially those that use financial ratio analysis tools, let alone literature that examines differences in financial performance based on land strata, especially in the context of liquidity and profitability, which are influenced by the size and condition of the farming land used. The research involved 26 curly red chili farmer respondents of narrow, medium, and large land area strata. The liquidity ratio is a measure used to assess the ability of a business to meet its short-term obligations using its current assets. The profitability ratio measures the extent to which a business can generate profits from sales or total assets owned. The research results show that the liquidity ratio of curly red chili farming in the three strata of land area is reasonable, with the Current Ratio and Cash Ratio values ​​greater than 1, which indicates that this farming can fulfill its short-term obligations well. The profitability ratio of curly red chili farming in Suka Sari Village is good with NPM values ​​> 15%, GPM > 20%, RoA > 8%, and RoE > 20%, which means farming has large profits so it is suitable for use as a commercial business. This research recommends that farmers maintain or improve their financial management, especially in managing costs and resources, to support the continuity and sustainability of the curly red chili farming business in Suka Sari Village.